Strategi Penyiaran Program Kelas Malam di 90.8FM OZ Radio Jakarta dalam Menarik Minat Pendengar - Amizur, Dhewara Ahmadi; Muhammad, R. Hiru (PT Literasi Nusantara Publisher, 2023)
This study discusses the Broadcasting Strategy implemented by 90.8FM OZ Radio Jakarta radio station in the Evening Class Program. OZ Radio Jakarta has a vision of becoming a role model radio station in Jakarta and nationally, but competition in the competitive radio industry requires them to take strategic steps. Moreover, OZ Radio Jakarta, which had stopped operating, had to be faced with the development of the current digitalization era. In this study, the theory of Broadcasting Strategy is used which includes aspects of program planning, Compability Strategy, Habbit Formation Strategy, Mass Appeal Strategy, and Conservation of Program Resources Strategy. This study uses a qualitative approach with descriptive methods and collects data through interviews, observation, and documentation. Purposive sampling technique was used in determining research informants. The results of the study show that through the Evening Class Program, OZ Radio Jakarta has succeeded in presenting relaxed chats that are in accordance with the lives of the target audience, in a simple and relaxed format. The success of the program is measured through the growth of listeners and interactions from social media and directly. Through implementing the right strategy, OZ Radio Jakarta has managed to consistently attract listeners and maintain a loyal listener base. The Kelas Malam program has helped this radio station rebuild its existence after it had stopped operating for a while. Overall, this study illustrates how OZ Radio Jakarta succeeded in implementing an effective Broadcasting Strategy in achieving their goals as an influential radio station in Jakarta and nationally. This made the researcher interested in conducting research with the title